Factors influencing the financial situation and management of small and medium enterprises - Nurul Mohammad Zayed; Isse Sudi Mohamed; Khan Mohammad Anwarul Islam; Iryna Perevozova; Vitalii Nitsenko; Olena Morozova (Journal of Risk and Financial Management, 2022)
The ambition of this study was to identify the factors that influence the financial situations of small and medium enterprises (SMEs) in Somalia. The research objectives of this study were to determine how capital building affected the financial situations of SMEs in Somalia, how human resource capacity affected the financial situations of SMEs, and what the impact of access to financing was according to the business conditions of SMEs. This study uses both descriptive and quantitative research approaches. The study's main demographics consisted of 90 SMEs in Somalia; the shortage of female personnel may also be a disadvantage, considering that most paying customers were female. The study's first research question was to investigate whether the use of committees improves the quality and efficiency of the board's tasks and mandates. The study's second research question was to determine the impact of human resources. The study's findings about market adoption of technological trends also revealed a strong positive relationship between human resource performance and financial performance. The Somali government should implement SME policies based on development and new growth industries, such as migration. Investment and credit firms, such as private sector banks and donor organizations, should lower the requirements for their investments. SME owners and managers should hire educated staff and increase the number of female employees. SME owners and managers should develop training schedules focusing on financial management, innovation, communication, and promotional abilities.
Keywords: 650; SMEs; financial development; employment creation in small and medium-sized businesses; financial management practice; governance on financial performance of SMEs